Population dynamics of Malabar sole Cynoglossus macrostomus Norman along Calicut coast - Khan, M Feroze; Nandakumaran, K (Indian Journal of Fisheries, 2011)
The flatfishes constitute a major fishelyalong Calicut coast and enjoy considerablelocal importance next to oilsardine andmackerel. Norman (1927, 1928) described91 species, of which only a few form fisheryof local importance. The most importantspecies in the commercial fishery isCynoglossus macrostomus Norman, locallyknown as mantha